Regional Autonomy from the Perspective of Capitalist Management - Sumarna, Andri; Haryono, Merda Budi; Fauzi, Sudar; Emuh, Dadang; Maulana, Dede (Jurnal Economic Resource, 2023)
Regional autonomy in Indonesia is expected to be an instrument for improving public welfare, equitable development, and strengthening governance. However, in practice, this policy is often distorted by the pragmatic interests of regional leaders who tend to adopt capitalist logic for personal or group gain. This condition is exacerbated by high political costs in regional elections, which encourage political behaviour that rewards capital and ignores public interests. This study aims to analyse regional autonomy from a capitalism management perspective and identify its implications for community welfare and governance. The study uses a qualitative method with a library research approach, examining sources such as books, scientific journals, legislation, and relevant research reports. Data analysis is conducted descriptively and analytically through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that regional autonomy, without regulatory reinforcement and leadership integrity, has the potential to become a tool of capitalist hegemony at the local level. Regional policies are often directed towards facilitating the interests of large capital, both national and foreign, which exploit natural and human resources, making it difficult to realise the ideals of social welfare as mandated by the 1945 Constitution. The implications of this research emphasise the need for low-cost political reform, strengthening governance based on Pancasila values, and moral education to foster integrity among local leaders.